Language and content : discipline-and content-based approaches to language study (D.C. Heath, 1993)
This book is divided into five parts: Introduction; Theoretical and research issues of discipline based approaches to language stidy; Case studies of exemplary programs; Implications for instructionak methods and materials; and Implications for the discipline and profession.